2021
DOI: 10.3389/fendo.2021.746838
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Diabetic Kidney Disease Mouse Model Culturing Embryos in α-Minimum Essential Medium In Vitro, and Feeding Barley Diet Attenuated the Pathology

Abstract: Diabetic kidney disease (DKD) is a critical complication associated with diabetes; however, there are only a few animal models that can be used to explore its pathogenesis. In the present study, we established a mouse model of DKD using a technique based on the Developmental Origins of Health and Disease theory, i.e., by manipulating the embryonic environment, and investigated whether a dietary intervention could ameliorate the model’s pathology. Two-cell embryos were cultured in vitro in α-minimum essential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Zeng et al [1] summarized the health effects of 22 chronic diseases of prevention and treatment, including antidiabetes, antiobesity, anticancer, antioxidants, improve gastrointestinal [49], antiinflammation, lower blood pressure, hepatoprotection, immunomodulation, alleviates atopic dermatitis, prevent cardiovascular diseases, hyperlipidemia, antiaging, cardioprotection, antifatigue, optimize cholesterol, improve bowel health, metabolic syndrome, prevent heart disease, reduce chronic kidney disease [50], accelerate wound healing, decrease stroke and cholelithiasis activities. Barley and adlay are the largest functional food with the use of 110 kinds of homologous substances in China, both barley grasses and grains can prevent and control more than 22 chronic diseases in humans or animals, due to molecular mechanism of barley grass (GABA, flavonoids, SOD, K-Ca, vitamins, and tryptophan) and grains (β-glucans, polyphenols, arabinoxylan, phytosterols, tocols, and resistant starch), especially support that human has only one cell disease theory, which provides a reference for the development of human functional food and animal husbandry production of functional feed [1,51].…”
Section: Barley Grains With 22 Health Effectsmentioning
confidence: 99%
“…Zeng et al [1] summarized the health effects of 22 chronic diseases of prevention and treatment, including antidiabetes, antiobesity, anticancer, antioxidants, improve gastrointestinal [49], antiinflammation, lower blood pressure, hepatoprotection, immunomodulation, alleviates atopic dermatitis, prevent cardiovascular diseases, hyperlipidemia, antiaging, cardioprotection, antifatigue, optimize cholesterol, improve bowel health, metabolic syndrome, prevent heart disease, reduce chronic kidney disease [50], accelerate wound healing, decrease stroke and cholelithiasis activities. Barley and adlay are the largest functional food with the use of 110 kinds of homologous substances in China, both barley grasses and grains can prevent and control more than 22 chronic diseases in humans or animals, due to molecular mechanism of barley grass (GABA, flavonoids, SOD, K-Ca, vitamins, and tryptophan) and grains (β-glucans, polyphenols, arabinoxylan, phytosterols, tocols, and resistant starch), especially support that human has only one cell disease theory, which provides a reference for the development of human functional food and animal husbandry production of functional feed [1,51].…”
Section: Barley Grains With 22 Health Effectsmentioning
confidence: 99%
“…Polygenic models, namely KK and KK AY mice, OLETF rats, NZO mice, etc., are characterized by obesity-induced hyperglycemia, severe hyperinsulinemia, IR in both muscle and adipose tissue, and pronounced changes in the pancreatic islets: from hypertrophy and degranulation to fibrosis and their replacement by the connective tissue [ 67 , 68 , 69 , 70 ]. A number of works focused on the elimination of T2DM symptoms, analysis of the relationship between obesity and glucose homeostasis, as well as diabetic complications, have been done using polygenic models [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Genetic Models With Obesitymentioning
confidence: 99%
“…26,80 These results imply that the "MEM mouse" can be used as a novel animal model for human diabetes. [14][15][16] Although the underlying mechanisms induced by αMEM medium remain unknown, unlike KSOM-AA, this αMEM medium has no protein such as bovine serum albumin (BSA) while containing vitamins such as folic acid (Table 1). Considering that BSA in culture media plays an important role beyond a source of amino acids, 81 its absence may contribute to inducing the phenotype.…”
Section: Perinatal and Long-term Outcomes Associated With Ivf/ivcmentioning
confidence: 99%
“…Recently, we have reported that mice derived from embryos treated with just αMEM medium, which is commonly used for mammalian cell culture, over 48 h, so‐called the “MEM mouse” exhibit increased weight with severe type 2 diabetes‐related phenotypes such as postprandial hyperglycemia, high inflammation gene expression, non‐alcoholic fatty liver disease, DKD, diabetic steatohepatitis, which are not observed in mice derived from embryos cultured in KSOM‐AA (mKSOM) medium, a KSOM medium supplemented with amino acids (Figure 3). 26,80 These results imply that the “MEM mouse” can be used as a novel animal model for human diabetes 14–16 . Although the underlying mechanisms induced by αMEM medium remain unknown, unlike KSOM‐AA, this αMEM medium has no protein such as bovine serum albumin (BSA) while containing vitamins such as folic acid (Table 1).…”
Section: Effects Of In Vitro Culture On Future Healthmentioning
confidence: 99%
See 1 more Smart Citation